Recent Advances in Natural Hydrolates for Burn Care: Anti-Inflammatory, Antioxidant and Antimicrobial Perspectives - Skovorodko, Polina; Parshenkov, Mikhail A; Ignatichev, Ivan; Abyshev, Togrul; Alypkacheva, Pasiyat; Bakaeva, Ekaterina; Borga, Eva; Tsibizova, Anna; Bekveriia, Nino; Simonyan, Manas; Abdulatipova, Salikhat (Scripta Medica, 2025)
Burn injuries represent a significant global health burden, characterised by complex pathophysiology that extends far beyond the initial thermal insult. The healing process is profoundly influenced by a cascade of molecular and cellular events, including acute and chronic inflammation, oxidative stress and microbial colonisation. These interconnected challenges frequently lead to severe complications such as delayed wound closure, impaired tissue regeneration and pathological scarring. A critical and escalating issue in contemporary burn care is the pervasive rise of antibiotic resistance, which severely compromises treatment efficacy, prolongs hospital stays and significantly increases both patient morbidity and mortality. This literature review critically examines the multifaceted aspects of burn wound healing, focusing on the intricate interplay between inflammation, oxidative stress and infection. It delves into the molecular mechanisms underlying these processes, including the dual role of reactive oxygen species (ROS) in cellular signalling and tissue damage and the dysregulation of key pathways that perpetuate chronic inflammation and promote fibrosis. The alarming rise of multidrug-resistant pathogens (eg Pseudomonas aeruginosa, Klebsiella pneumoniae, Staphylococcus aureus, etc) further exacerbates these challenges, highlighting the urgent need for novel therapeutic strategies. The limitations of conventional therapies in precisely modulating these complex biological processes and effectively countering resistant microorganisms are thoroughly discussed. Special attention is given to the therapeutic potential of natural compounds, particularly hydrolates, as innovative and complementary interventions. Current evidence in specific literature demonstrates their anti-inflammatory, antioxidant and antimicrobial properties, supporting their capacity to create a favourable healing microenvironment and mitigate the impact of antibiotic resistance. By elucidating the mechanisms through which these botanical extracts may influence wound healing, this review seeks to identify critical knowledge gaps and provide a robust foundation for future research into integrative approaches that can optimise burn wound outcomes and address urgent clinical needs.